Presumed Validity of Marriage when a Party has Died: Canon 1675 - Ingles, Gregory (CLSA advisory opinions, 2001-2005, 2001)
A non-Catholic petitioner has been married three times. All three marriages ended in divorce, and now this party wishes to enter into marriage with a Catholic. A unique circumstance in this case is that the petitioner's first spouse died following the party's third and final divorce. Since the validity of a marriage bond cannot be challenged following the death of a spouse, can the presumed validity which this first bond enjoys be used as the basis for declaring the invalidity of the petitioner's second and third marriages on the basis of the impediment of previous bond of marriage?